The death penalty: documents decoded - Melusky, Joseph A. (Documents decoded, 2013)
"When is the death penalty considered "cruel and unusual punishment" or "constitutionally permissible"? This book exposes readers directly to landmark opinions of the U.S. Supreme Court that strive to answer difficult questions regarding capital punishment"--